The emerging role of neutrophil extracellular traps in ulcerative colitis - Long, Dan; Mao, Chenhan; Xu, Yin; Zhu, Ying (Frontiers in Immunology, 2024)
Ulcerative colitis (UC) is characterized by chronic non-recessive inflammation of the intestinal mucosa involving both innate and adaptive immune responses. Currently, new targeted therapies are urgently needed for UC, and neutrophil extracellular traps (NETs) are new therapeutic options. NETs are DNA-based networks released from neutrophils into the extracellular space after stimulation, in which a variety of granule proteins, proteolytic enzymes, antibacterial peptides, histones, and other network structures are embedded. With the deepening of the studies on NETs, their regulatory role in the development of autoimmune and autoinflammatory diseases has received extensive attention in recent years. Increasing evidence indicates that excess NETs exacerbate the inflammatory response in UC, disrupting the structure and function of the intestinal mucosal barrier and increasing the risk of thrombosis. Although NETs are usually assigned a deleterious role in promoting the pathological process of UC, they also appear to have a protective role in some models. Despite such progress, comprehensive reviews describing the therapeutic promise of NETs in UC remain limited. In this review, we discuss the latest evidence for the formation and degradation of NETs, focusing on their double-edged role in UC. Finally, the potential implications of NETs as therapeutic targets for UC will be discussed. This review aims to provide novel insights into the pathogenesis and therapeutic options for UC.